1984
DOI: 10.1111/j.2042-7158.1984.tb04373.x
|View full text |Cite
|
Sign up to set email alerts
|

In―vitro evaluation of the anticandidiasis activity of honey distillate (HY−1) compared with that of some antimycotic agents

Abstract: The susceptibility of 72 isolates of Candida albicans to the antimicrobial honey distillate fraction (HY-1) and several antimycotic agents is presented. All the isolates were sensitive to HY-1, H-115 and Jadit, while about 10% of the isolates were variably resistant to nystatin, miconazole nitrate and clotrimazole. The nystatin, miconazole nitrate and clotrimazole resistant isolates were inhibited by HY-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 2 publications
2
25
1
Order By: Relevance
“…The types of skin wounds treated were also rather limited, but these were included in the 24 wound types mentioned by the National Honey Board review (Molan, 1999a). Researchers have shown antimicrobial activity in honey (Obaseiki-Ebor et al, 1983;Obaseiki-Ebor and Afonya, 1984;Willix et al, 1992;Krell, 1996;Molan, 1998;Molan, 1999a,b;Molan and Betts, 2000;Nzeako and Hamdi, 2000;Subrahmanyam et al, 2001;Mathews and Binnington, 2002) and have also used it for treating surgical wounds, skin ulcers, abscesses (Molan, 1999a) and burn wounds. Good histological preservation of skin grafts after honey treatment has also been described (Subrahmanyam, 1993).…”
Section: Topical Applicationmentioning
confidence: 99%
“…The types of skin wounds treated were also rather limited, but these were included in the 24 wound types mentioned by the National Honey Board review (Molan, 1999a). Researchers have shown antimicrobial activity in honey (Obaseiki-Ebor et al, 1983;Obaseiki-Ebor and Afonya, 1984;Willix et al, 1992;Krell, 1996;Molan, 1998;Molan, 1999a,b;Molan and Betts, 2000;Nzeako and Hamdi, 2000;Subrahmanyam et al, 2001;Mathews and Binnington, 2002) and have also used it for treating surgical wounds, skin ulcers, abscesses (Molan, 1999a) and burn wounds. Good histological preservation of skin grafts after honey treatment has also been described (Subrahmanyam, 1993).…”
Section: Topical Applicationmentioning
confidence: 99%
“…About 50 毺 L of the different concentrations (undiluted, 30%, 50% and 70% w/v) of the honey samples were separately placed in the different punched wells with 1 mL sterile syringe. The plates were allowed to stay for 15 min for pre-diffusion to take place followed by an overnight incubation that lasted for 24 h at 37 曟. The diameter of inhibition zones, including the diameter of the well, was recorded.…”
Section: Antifungal Assaymentioning
confidence: 99%
“…The in vitro antifungal activity of honey was reported by Maria et al [23] , who observed that honey stops the growth of C. albicans, Candida krusei and Cryptococcus neoformans. Obaseik-Ebor and Afongo [24] compared the antifungal activity of honey distillate with some antimycotic preparations against C. albians and found that all the strains resistant to conventional antimycotic agents are inhibited by the active fraction of honey distillate.…”
Section: Introductionmentioning
confidence: 99%
“…[97] Candidiasis, triggered by Candida albicans, may respond to honey. [98] Superficial and cutaneous mycoses like athlete's foot and ringworm are found to be responsive to honey. This responsiveness is owing to the inhibition of bacterial infection and restriction of mycological growth.…”
Section: Honey In Primeval Greecementioning
confidence: 99%
“…In infective conjunctivitis, application of honey reduced inflammation, discharge of pus, time to bacterial eradication and redness. [13,98] Honey and diabetes mellitus Honey has been indicated to reduce hyperglycaemia and scavenge reactive oxygen species. [102,103] There is dose dependency in hypoglycaemic effect whereas supplemented honey improves oxidative stress with no dependency on dose.…”
Section: Honey In Primeval Greecementioning
confidence: 99%